L’écriture confidentielle. Réalité et chimère - Elena Mihaela Andrei∗ (Journal of Humanistic and Social Studies, 2016)
The article puts in parallel the casualness of Restif de la Bretonne with regard to the dissoluteness and to the confidential writing and the vision of Nerval towards the practice of the loving confessions. The analysis concentrates on some passages, the most suggestive, pulled by the Voyage en Orient et des Nuits d’octobre, more exactly “Amours de Venise”, as well as of Aurélia to show how Nerval crosses the way from the biography to the autobiography, falls and looks for himself in the portrait of his character